Peran Guru PAI sebagai Murabbi dalam Membangun Akhlak di Era Disrupsi Teknologi - Nayla Shofiyyatul Umaami; Syamsul Aripin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid development of digital technology has had a significant impact on the behavior, morals, and ways of thinking of the younger generation. In this context, Islamic Religious Education (PAI) teachers not only act as instructors (mu'allim), but also as murabbi who foster and instill moral values. This article aims to emphasize the importance of the role of PAI teachers as moral educators in facing the era of technological disruption. The research method uses a descriptive qualitative approach with a literature study from various journals and books related to modern Islamic education. The results of the study indicate that the role of PAI teachers as murabbi encompasses three main aspects: (1) spiritual role models, (2) character development based on Islamic values, and (3) utilization of technology as a medium for da'wah and moral education. By combining traditional Islamic values and digital innovation, PAI teachers can maintain the relevance of Islamic education amidst the challenges of modernization.